Clinical characteristics, management, and outcomes of patients with electrical storm: single centre experience. (14th October 2021) - Di Fusco, S.A; Pignalberi, C; Spinelli, A; Baca, M; Cappuccio, C; Russo, M; Pandozi, C; Colivicchi, F
Abstract: Background: Electrical storm (ES) is a life-threatening condition caused by recurrent malignant ventricular arrhythmia (≥3 episodes of ventricular tachycardia (VT) or ventricular fibrillation within 24 hours). ES patient management is challenging and can involve antiarrhythmic medication, sedation, and invasive procedures such as catheter ablation. Purpose: The aim of this study is to report the clinical profile and management of ES patients who attended an arrhythmia reference centre. Methods: Patients who presented with ES at our centre over a five-year period were consecutively enrolled. Patient data were retrospectively collected from hospital records. Patients with in-hospital death were excluded form data analysis. Results: Seventy-six patients were included (84% male, mean age 73±10 years). 55% of patients had ischemic heart disease. The mean left ventricle ejection fraction (LVEF) was 33±4%, with 22% of patients having a severe reduction in systolic ventricular function (EF <35%). Baseline characteristics are reported in Table 1. During hospitalisation, 30% of patients underwent coronary angiography and 30% of these had percutaneous coronary revascularization. Patients were managed with pharmacological treatment, including continuous infusion of antiarrhythmic drugs (45% of patients received at least one antiarrhythmic), sedation (12%), and electrolytic solutions (38%). More details on ES management are reported in Table 2. All patients were evaluated for transcatheter ablation. After a mean of 6 days, 25% underwent transcatheter VT ablation during hospitalisation. In 7 patients (9%), catheter ablation was planned and performed during a subsequent hospitalisation. At discharge, 93% of patients received beta blockers and 68% received amiodarone. Overall, 65% were discharged with at least two antiarrhythmic drugs. The mean length of hospitalisation was 10±9 days, with 6±4 days spent in the intensive care unit. Eighteen patients (23%) had at least one subsequent hospitalisation for ES. After a mean follow-up of 20 months, the cumulative mortality rate was 27%, without a significant difference in mortality rates between ablated and non-ablated patients (27% and 28%, respectively). Baseline mean creatinine levels were higher (1.73±1.1 vs. 1.27±0.1 mg/dl, p<0.05), and LVEF was lower (27±3% vs. 35±17%, p<0.05) in patients who died during follow-up as compared to survivors. A trend toward a longer QTc interval duration (482±47 vs. 467±28 ms) and longer QRS duration (139±36 vs. 131±7 ms) was also found among patients who died during follow-up. Conclusion: In our centre, ischemic heart disease was the most common heart disease in patients presenting with ES. In more than one third of patients, VT transcatheter ablation was performed as a therapeutic strategy in addition to drug therapy. Among patients who died during the follow-up, baseline creatinine levels were higher and LVEF was lower compared with survivors. Funding Acknowledgement: Type of funding sources: None.